Reliability and Validity of Facial Check Sheet (FCS): Checklist for Self-Satisfaction with Cosmetic Acupuncture - Hiroshi Kuge; Hidetoshi Mori; Tim Hideaki Tanaka; Ryouta Tsuji (Medicines, 2021)
Background: In recent years, cosmetic acupuncture has gained popularity among individuals interested in improving their facial appearance. We have created an original facial check sheet (FCS) to obtain cosmetic acupuncture patients’ perspectives on treatment outcomes. This study examined the reliability and validity of FCS. Methods: We conducted an Internet survey on the appearance of the facial region among Japanese women. A reliability analysis was performed between each item of FCS. A multiple comparison procedure was used to determine the relationship between the age group, the FCS score, and the number of terms used in the open-ended question. Results: The most frequently stated concern was blotchiness and hyperpigmented spots (47.2%, n = 67). The FCS items showed reliability (Cronbach α = 0.871). The number of extracted terms and the FCS score showed a moderate correlation (r = 0.407; p < 0.001). There was a significant relationship between age and FCS score (p = 0.005, r2 = 0.255), which indicated that the FCS score increases with aging. Conclusions: The FCS can be used as a practical tool to evaluate facial appearances and assess satisfaction levels of patients who underwent cosmetic acupuncture or other facial skin rejuvenation procedures.